Continuous Health Monitoring System for Remote Patients using ATmega328 - Ms. Adlene P., Mr. Saurav Chaudhuri, Ms. Anideepa Mitra (International Journal of Advanced Science and Technology, 2020)
Seeing the rising trend of automation and also the health condition around the globe the project aims in linking both the medical industry and also the engineering industry together. The project aims at the design of a very low cost continuous health monitoring system which measures the primary health measurements and their alerts and notifies the doctor about the above and take necessary steps according to the readings. During a time of emergency the patient can be treated accurately by the doctor and quick actions will also be taken. This continuous health measuring system is driven by microprocessor ATmega328. The system has several sensors such as a sensor used for measuring heart rate along with the temperature of the system, this measured data is stored in a database and then uploaded in a cloud based platform. The heartbeat and temperature data is uploaded on two page 1-Doctor 2-Patient’s relative. Threshold value for both temp and heartbeat is set and alert is send to both doctor and relative along with a buzzer once the threshold crosses Equipment used: Arduino board, Heart rate sensor, Temperature sensor LM35, Microsoft visual C++, Zigbee and GSM model- MGSM900, PDA.